Feminist thought and economics; or, what do the Visigoths know? - Strassman, Diana L. (American Economic Review, 1994)
Many economists have expressed concern that approaches borrowed from the humanities or from the softer social sciences will detract from the rigor and objectivity of economic science and give voice to those without proper training-and in so doing reduce the discipline to a science no more defensible than alchemy. Since much feminist thought in economics draws heavily from intellectual traditions alien to mainstream economists (e.g. critical interpretive theory, cultural studies, and feminist theory), some economists may wonder what such modes of inquiry have to offer economics.' Further, they may ask, are there no pitfalls in modes of inquiry not disciplined by accepted economic methodologies? In short, what do those Visigoths know? My purpose is to address issues in method and theory underlying recent feminist work in economics, and to explain how economics may gain by opening its disciplinary gates. From the perspective of traditional mainstream practice in economics, two prominent issues emerge in considering modes of inquiry and theory drawn from other disciplines. The first has to do with what counts as theory and the role of critique in theorizing. The second has to do with the need to sort out better theories from worse and the perceived dangers of rampant relativism. I will address these in turn.